The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1002/iid3.330
|View full text |Cite
|
Sign up to set email alerts
|

Necroptotic‐susceptible dendritic cells exhibit enhanced antitumor activities in mice

Abstract: Introduction: Priming of tumor-specific T cells is a key to antitumor immune response and inflammation, in turn, is crucial for proper T-cell activation. As antigen-presenting cells can activate T cells, dendritic cells (DCs) loaded with tumor antigens have been used as immunotherapeutics against certain cancer in humans but their efficacy is modest. Necroptosis is a form of programmed cell death that results in the release of inflammatory contents. We previously generated mice with DC deficiency in a negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…Traditional anticancer drugs are currently being developed to target relevant steps in the necroptosis pathway to promote or inhibit necroptosis signaling in tumor cells [16][17][18][19]. Several studies have reported that the activation of necroptotic cell death in tumors could increase DC activation and T cell in ltration, which synergistically act with immune check-point inhibitors to enhance antitumor e ciency that promotes long-lasting tumor clearance [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional anticancer drugs are currently being developed to target relevant steps in the necroptosis pathway to promote or inhibit necroptosis signaling in tumor cells [16][17][18][19]. Several studies have reported that the activation of necroptotic cell death in tumors could increase DC activation and T cell in ltration, which synergistically act with immune check-point inhibitors to enhance antitumor e ciency that promotes long-lasting tumor clearance [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…FADD is a negative regulator of necroptosis. A higher number of activated CD8 + T cells and elevated levels of cytokines were observed in mice injected with the FADD-de cient DC vaccine; thus, FADD can be used to reduce tumor growth in combination with anti-PD-1 antibodies [23]. Staining of cholangiocarcinoma tissues showed that, contrary to MLKL, pMLKL-positive samples were signi cantly positively correlated with favorable immune characteristics within the tumor microenvironment (that is, high abundance of CD8 + T cell in ltration) and high PD-L1 expression, and patients with high pMLKL and PD-L1 expression showed longer OS [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…123 Another study elegantly demonstrates that necroptosis-driven inflammation through DCs works in combination with anti-PD-1 antibodies to inhibit the proliferation of melanoma. 124 Similarly, in osteosarcoma, TNF-α-loaded liposomes induced ICD in tumour cells, leading to TNF-α-triggered necrosis, tumour-specific antigen release, enhanced DC activation, and T cell infiltration when combined with anti-PD-1/PD-L1 therapy. 125 Various stresses regulate PD-L1 expression, promoting cancer progression and impacting patient survival rates.…”
Section: Necroptosis In Anti-pd1/pd-l1 Immunotherapymentioning
confidence: 99%
“…This small molecule‐induced Z‐DNA turnover activated ZBP1, culminating in RIPK3‐mediated necroptosis and immune system engagement against the tumour 123 . Another study elegantly demonstrates that necroptosis‐driven inflammation through DCs works in combination with anti‐PD‐1 antibodies to inhibit the proliferation of melanoma 124 . Similarly, in osteosarcoma, TNF‐α‐loaded liposomes induced ICD in tumour cells, leading to TNF‐α‐triggered necrosis, tumour‐specific antigen release, enhanced DC activation, and T cell infiltration when combined with anti‐PD‐1/PD‐L1 therapy 125 …”
Section: Regulatory Cell Death In Anti‐pd1/pd‐l1 Therapymentioning
confidence: 99%